FAKTOR EKSTERNAL YANG BERHUBUNGAN DENGANSAFETY DRIVING PADA PENGEMUDI ANGKUTAN KOTA/OPLET PO. BAYU PUTRA DI KOTA PEKANBARU - LPPM Al-Insyirah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2016)
In Indonesia, the transportation is growing rapidly in terms of both quality and quantity, This development was not entirely positive impact but also creates its own problems such as congestion due to an increase in the number of vehicles is not accompanied by the addition of roads, especially at rush hour leave and come home from work , the condition is exacerbated by the behavior of motorists both cars and motorcycles that do not comply with regulations, coupled with burukmya condition of the vehicle as well as damage to infrastructure such as roads. This study aims to determine the relationship between driver behavior, vehicle condition and road conditions to the driver's driving safety on public transportation / oplet PO Bayu Putra in Pekanbaru. Methods This study uses a quantitative approach to quantitative research with cross sectional design in that the data is collected only when after doing research. The sample used is public transportation drivers / oplet PO Bayu Putra in Pekanbaru totaling 101. Results from this study that there is a significant relationship between driver behavior, vehicle condition and road conditions to the driver's driving safety on public transportation / oplet PO Bayu Putra City Pekanbaru. Rider behavior ρ values ​​obtained value 0.039, which means the value of ρ value <α (0.05), the condition of the vehicle obtained by the value of ρ value 0.004, which means the value of ρ value <α (0.05) and road conditions ρ values ​​obtained value 0.016, which means the value of ρ value <α (0.05) Ho refused meaning there is a statistically significant relationship.